A photocatalytic treatment method for industrial oily wastewater
By using dual core-shell structure photocatalysts in industrial oil-containing wastewater treatment, the problems of time-consuming and labor-intensive equipment and low pollutant removal rate in the prior art are solved, and efficient and environmentally friendly wastewater treatment effects are achieved.
Patent Information
- Application Number
- CN202411686501.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The prior art uses time-consuming and labor-intensive equipment when treating industrial oil-containing wastewater, low pollutant removal rate, and problems such as secondary pollution and long treatment cycle.
A double core-shell structure photocatalyst is used, including bimetallic sulfides (such as MCo2S4, M is Fe, Ni, Cu, Zn) as the core body, titanium dioxide as the intermediate shell layer, and perovskite oxide as the outer shell layer, and industrial oil-containing wastewater is treated by photocatalytic treatment.
It improves photocatalytic activity and charge transfer and separation efficiency, significantly improves the treatment effect of industrial oil-containing wastewater, avoids secondary pollution, and simplifies the process flow.
Smart Images

Figure CN119191454B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, in particular to a photocatalytic treatment method for industrial oily wastewater. Background Art
[0002] Industrial oily wastewater is produced in large quantities and from a wide range of sources. The oil in the wastewater generally exists in three states: floating oil, dispersed oil and emulsified oil. Oil pollution has adverse effects on humans, animals, plants and even the entire ecosystem.
[0003] Industrial oily wastewater will settle in industrial facilities and pipelines together with suspended particles in the wastewater, forming viscous sludge, which will block pipelines and equipment and affect the normal production. It will also form an oil film on the water surface, causing a decrease in dissolved oxygen in the water body, limiting algae photosynthesis, affecting the normal growth of aquatic organisms, and polluting the surface water, soil and groundwater of rivers, lakes, and rivers. In waters polluted by oily wastewater, a large number of fish and birds died due to suffocation or skin contamination by oil. When oily wastewater flows into farmland, the oil film will cover the surface of soil and plants, block the gaps in the soil, prevent air from penetrating, and prevent animals, plants and microorganisms in the soil from normal metabolism. It will not only cause agricultural product pollution, reduced production or death, but also migrate under the soil, which may cause serious groundwater pollution.
[0004] At present, the methods for treating industrial oily wastewater can be roughly divided into physical methods, chemical methods and biological methods. Among them, the physical method is the most commonly used method for treating industrial oily wastewater pollution, but the oil containment method and mechanical method require the assistance of large equipment, which is time-consuming and labor-intensive, and the pollutant removal rate is low. Chemical methods can effectively remove pollution, but the flocculation method can easily cause secondary pollution. The biological method is greatly affected by the surrounding environment, has a slow reaction, and a long treatment cycle.
[0005] As one of the chemical methods, photocatalytic degradation technology has the advantages of simple process, no secondary pollution, and high efficiency. How to use photocatalytic degradation technology to efficiently treat industrial oily wastewater has become a research hotspot for scientific researchers. Summary of the invention
[0006] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for photocatalytic treatment of industrial oily wastewater.
[0007] The technical solutions adopted are as follows:
[0008] A photocatalytic treatment method for industrial oily wastewater:
[0009] Adding double core-shell structure photocatalyst to industrial oily wastewater and continuously providing light for photocatalytic treatment;
[0010] The double core-shell structure photocatalyst uses a double metal sulfide as a core;
[0011] Titanium dioxide is used as the middle shell;
[0012] The outer shell layer is perovskite oxide.
[0013] Furthermore, the bimetallic sulfide is MCo 2 S 4 , where M is a transition metal element.
[0014] Furthermore, M is any one of Fe, Ni, Cu and Zn.
[0015] Furthermore, the bimetallic sulfide is modified by carbon material.
[0016] Furthermore, the amount of carbon material used is 1-50% of the amount of the bimetallic sulfide.
[0017] Furthermore, the carbon material is carbon nanotube and / or nanographene.
[0018] Furthermore, the structural formula of the perovskite oxide is as follows:
[0019] Bi 0.5 Na 0.5 Ti 1-x (Zr 0.5 Ce 0.5 ) x O 3;
[0020] Among them, 0<x≤0.1.
[0021] Further, 0.04≤x≤0.06.
[0022] x can be 0.04, 0.041, 0.042, 0.043, 0.044, 0.045, 0.046, 0.047, 0.048, 0.049, 0.05, 0.051, 0.052, 0.053, 0.054, 0.055, 0.056, 0.057, 0.058, 0.059, 0.06. The above list is only for ease of understanding and does not limit the technical solution of the present invention.
[0023] Furthermore, the preparation method of the double core-shell structure photocatalyst is as follows:
[0024] The water-soluble cobalt salt, the water-soluble M salt and the thioacetamide are dissolved in the N-methylpyrrolidone / water mixed solution, and then the carbon material is added, and the temperature is raised to 160-180°C for hydrothermal reaction for 5-10 hours in a sealed state, and the product is collected, washed with deionized water and anhydrous ethanol and dried, and then annealed at 350-450°C for 1-5 hours to obtain a core body, and then a titanium dioxide precursor impregnation solution and a perovskite oxide precursor impregnation solution are prepared respectively by the solution gel method, and the core body is successively impregnated in the titanium dioxide precursor impregnation solution and the perovskite oxide precursor impregnation solution, dried and then heat treated.
[0025] Furthermore, the heat treatment temperature is 550-650°C.
[0026] Furthermore, the dosage of the double core-shell structure photocatalyst is 0.1-1 g / L.
[0027] The dosage of the double core-shell structure photocatalyst is 0.1g / L, 0.2g / L, 0.3g / L, 0.4g / L, 0.5g / L, 0.6g / L, 0.7g / L, 0.8g / L, 0.9g / L, and 1g / L. The above list is only for ease of understanding and does not limit the technical solution of the present invention.
[0028] Beneficial effects of the present invention:
[0029] The present invention provides a method for photocatalytic treatment of industrial oily wastewater. In the present application, the core and shell of the double core-shell structure photocatalyst have three-dimensional contact, and the shells have three-dimensional contact, which can maximize the interface contact area of the heterojunction, inhibit the recombination of photogenerated electron-hole pairs, and help improve the charge transfer and separation efficiency, so that it has high photocatalytic activity and excellent treatment effect on industrial oily wastewater.
[0030] Carbon material modification of bimetallic sulfides can improve the conductivity of bimetallic sulfides, effectively reduce the resistance of electron transmission, and improve the migration rate of electrons in the nucleus, thereby enhancing the efficiency of photocatalytic reactions;
[0031] Perovskite oxides have octahedral transport channels for carriers, and the interlayers can accommodate a large amount of organic and inorganic substances, so they have broad application prospects in photocatalysis. The present application uses perovskite oxides as the outer shell layer, and the large contact area allows it to fully contact and react with industrial oily wastewater. The use of composite ions to dope it is conducive to the formation of oxygen vacancies, and oxygen vacancies are the source of interface carriers, which promotes the improvement of the photocatalytic activity of the catalyst.
[0032] In the present application, the sol-gel method is used to prepare the double core-shell structure to obtain a core-shell and shell-shell structure with strong connections. The interaction force between the various parts of the constructed material is strong, the interface contact is relatively stable, and the shell thickness can be adjusted by changing the impregnation parameters. After testing, the photocatalytic treatment method provided by the present invention has an excellent treatment effect on industrial oily wastewater and can be widely promoted and applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 TEM image of the double core-shell structure photocatalyst prepared in Example 1;
[0034] Figure 2 is a graph showing the change of oil removal rate over time in the photocatalytic treatment method of Example 1;
[0035] Figure 3 is a graph showing the change of oil removal rate over time in the photocatalytic treatment method of Example 2;
[0036] Figure 4 is a graph showing the change of oil removal rate over time in the photocatalytic treatment method of Example 3;
[0037] Figure 5 This is a curve chart showing the change of oil removal rate over time in the photocatalytic treatment method of Example 4. DETAILED DESCRIPTION
[0038] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0039] Embodiment 1:
[0040] A photocatalytic treatment method for industrial oily wastewater:
[0041] 4# fuel oil was added to deionized water to make a 1g / L solution to simulate industrial oily wastewater. 200ml of industrial oily wastewater was taken and 0.5g / L of double core-shell structure photocatalyst was added. It was first adsorbed in the dark for 30min. A 300W xenon lamp with a 420nm filter was used to simulate the visible light source. The light source was 30cm away from the wastewater surface. Stirring was continued during the photocatalytic treatment. 5ml of industrial oily wastewater was taken as a sample with a pipette every 10min. The mass concentration of oil was measured with an infrared spectrophotometer to calculate the oil removal rate. The results are as follows: Figure 2 shown.
[0042] Among them, the double core-shell structure photocatalyst is nanographene modified FeCo 2 S4 For the nuclear body;
[0043] Titanium dioxide is used as the middle shell;
[0044] Perovskite-type oxide Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05 O 3 For the outer shell layer;
[0045] The preparation method of the double core-shell structure photocatalyst is as follows:
[0046] 20mmol of cobalt nitrate hexahydrate, 10mmol of ferric nitrate nonahydrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, and mechanically stirred for 30min to make the mixture uniform, and then 0.5g of nanographene was added, and the mixture was sealed and heated to 180°C for hydrothermal reaction for 8h, and then returned to room temperature, and the product was collected, washed repeatedly with deionized water and anhydrous ethanol, and then dried, and then placed in a muffle furnace and heated to 350°C at a rate of 5°C / min and kept warm for 2h to obtain a core body;
[0047] 10 ml of butyl titanate was dropped into 35 ml of anhydrous ethanol, and stirred for 10 min to mix evenly to obtain liquid A. 10 ml of deionized water was added to another 35 ml of anhydrous ethanol, and stirred for 10 min. Then, glacial acetic acid was added to obtain liquid B with a pH of 2. Liquid B was kept stirred, and liquid A was slowly dropped into liquid B. After the dropping was completed, stirring was continued for 30 min. Then, stirring was stopped and the mixture was placed in a constant temperature water bath at 45°C for 30 min to obtain a titanium dioxide precursor impregnation solution. 1 g of the core was placed in the titanium dioxide precursor impregnation solution, and immersed for 10 min. Then, the intermediate was taken out and dried.
[0048] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 2.5mmol cerium nitrate hexahydrate was dissolved in 20ml deionized water to obtain liquid E, 95mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid F, 2.5mmol zirconium isopropoxide was dropped into 20ml anhydrous ethanol to obtain liquid G, liquid C, liquid D and liquid E were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, and After liquid F and liquid G are evenly mixed, 5 ml of ethylene glycol ethyl ether is added to obtain a second mixed solution. The first mixed solution is kept stirring, and the second mixed solution is slowly dripped into the first mixed solution. After the dripping is completed, the stirring reaction is continued for 30 minutes, and then the stirring is stopped and placed in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution. The intermediate is placed in the perovskite oxide precursor impregnation solution and immersed for 10 minutes. After taking out and drying, it is transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2 hours.
[0049] Embodiment 2:
[0050] A photocatalytic treatment method for industrial oily wastewater:
[0051] 4# fuel oil was added to deionized water to make a 1g / L solution to simulate industrial oily wastewater. 200ml of industrial oily wastewater was taken and 0.5g / L of double core-shell structure photocatalyst was added. It was first adsorbed in the dark for 30min. A 300W xenon lamp with a 420nm filter was used to simulate the visible light source. The light source was 30cm away from the wastewater surface. Stirring was continued during the photocatalytic treatment. 5ml of industrial oily wastewater was taken as a sample with a pipette every 10min. The mass concentration of oil was measured with an infrared spectrophotometer to calculate the oil removal rate. The results are as follows: Figure 3 shown.
[0052] Among them, the double core-shell structure photocatalyst is CuCo modified by nanographene 2 S 4 For the nuclear body;
[0053] Titanium dioxide is used as the middle shell;
[0054] Perovskite-type oxide Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05 O 3 For the outer shell layer;
[0055] The preparation method of the double core-shell structure photocatalyst is as follows:
[0056] 20mmol of cobalt nitrate hexahydrate, 10mmol of copper nitrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, and mechanically stirred for 30min to make the mixture uniform, and then 0.5g of nanographene was added, and the mixture was sealed and heated to 180℃ for hydrothermal reaction for 8h, and then returned to room temperature, and the product was collected, washed repeatedly with deionized water and anhydrous ethanol, and then dried, and then placed in a muffle furnace and heated to 350℃ at a rate of 5℃ / min and kept warm for 2h to obtain a core body;
[0057] 10 ml of butyl titanate was dropped into 35 ml of anhydrous ethanol, and stirred for 10 min to mix evenly to obtain liquid A. 10 ml of deionized water was added to another 35 ml of anhydrous ethanol, and stirred for 10 min. Then, glacial acetic acid was added to obtain liquid B with a pH of 2. Liquid B was kept stirred, and liquid A was slowly dropped into liquid B. After the dropping was completed, stirring was continued for 30 min. Then, stirring was stopped and the mixture was placed in a constant temperature water bath at 45°C for 30 min to obtain a titanium dioxide precursor impregnation solution. 1 g of the core was placed in the titanium dioxide precursor impregnation solution, and immersed for 10 min. Then, the intermediate was taken out and dried.
[0058] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 2.5mmol cerium nitrate hexahydrate was dissolved in 20ml deionized water to obtain liquid E, 95mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid F, 2.5mmol zirconium isopropoxide was dropped into 20ml anhydrous ethanol to obtain liquid G, liquid C, liquid D and liquid E were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, and After liquid F and liquid G are evenly mixed, 5 ml of ethylene glycol ethyl ether is added to obtain a second mixed solution. The first mixed solution is kept stirring, and the second mixed solution is slowly dripped into the first mixed solution. After the dripping is completed, the stirring reaction is continued for 30 minutes, and then the stirring is stopped and placed in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution. The intermediate is placed in the perovskite oxide precursor impregnation solution and immersed for 10 minutes. After taking out and drying, it is transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2 hours.
[0059] Embodiment 3:
[0060] A photocatalytic treatment method for industrial oily wastewater:
[0061] 4# fuel oil was added to deionized water to make a 1g / L solution to simulate industrial oily wastewater. 200ml of industrial oily wastewater was taken and 0.5g / L of double core-shell structure photocatalyst was added. It was first adsorbed in the dark for 30min. A 300W xenon lamp with a 420nm filter was used to simulate the visible light source. The light source was 30cm away from the wastewater surface. Stirring was continued during the photocatalytic treatment. 5ml of industrial oily wastewater was taken as a sample with a pipette every 10min. The mass concentration of oil was measured with an infrared spectrophotometer to calculate the oil removal rate. The results are as follows: Figure 4 shown.
[0062] Among them, the double core-shell structure photocatalyst is nanographene modified ZnCo 2 S 4 For the nuclear body;
[0063] Titanium dioxide is used as the middle shell;
[0064] Perovskite-type oxide Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05 O 3 For the outer shell layer;
[0065] The preparation method of the double core-shell structure photocatalyst is as follows:
[0066] 20mmol of cobalt nitrate hexahydrate, 10mmol of zinc nitrate hexahydrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, and mechanically stirred for 30min to make the mixture uniform, and then 0.5g of nanographene was added, and the mixture was sealed and heated to 180°C for hydrothermal reaction for 8h, and then returned to room temperature, and the product was collected, washed repeatedly with deionized water and anhydrous ethanol, and then dried, and then placed in a muffle furnace and heated to 350°C at a rate of 5°C / min and kept warm for 2h to obtain a core body;
[0067] 10 ml of butyl titanate was dropped into 35 ml of anhydrous ethanol, and stirred for 10 min to mix evenly to obtain liquid A. 10 ml of deionized water was added to another 35 ml of anhydrous ethanol, and stirred for 10 min. Then, glacial acetic acid was added to obtain liquid B with a pH of 2. Liquid B was kept stirred, and liquid A was slowly dropped into liquid B. After the dropping was completed, stirring was continued for 30 min. Then, stirring was stopped and the mixture was placed in a constant temperature water bath at 45°C for 30 min to obtain a titanium dioxide precursor impregnation solution. 1 g of the core was placed in the titanium dioxide precursor impregnation solution, and immersed for 10 min. Then, the intermediate was taken out and dried.
[0068] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 2.5mmol cerium nitrate hexahydrate was dissolved in 20ml deionized water to obtain liquid E, 95mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid F, 2.5mmol zirconium isopropoxide was dropped into 20ml anhydrous ethanol to obtain liquid G, liquid C, liquid D and liquid E were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, and After liquid F and liquid G are evenly mixed, 5 ml of ethylene glycol ethyl ether is added to obtain a second mixed solution. The first mixed solution is kept stirring, and the second mixed solution is slowly dripped into the first mixed solution. After the dripping is completed, the stirring reaction is continued for 30 minutes, and then the stirring is stopped and placed in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution. The intermediate is placed in the perovskite oxide precursor impregnation solution and immersed for 10 minutes. After taking out and drying, it is transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2 hours.
[0069] Embodiment 4:
[0070] A photocatalytic treatment method for industrial oily wastewater:
[0071] 4# fuel oil was added to deionized water to make a 1g / L solution to simulate industrial oily wastewater. 200ml of industrial oily wastewater was taken and 0.5g / L of double core-shell structure photocatalyst was added. It was first adsorbed in the dark for 30min. A 300W xenon lamp with a 420nm filter was used to simulate the visible light source. The light source was 30cm away from the wastewater surface. Stirring was continued during the photocatalytic treatment. 5ml of industrial oily wastewater was taken as a sample with a pipette every 10min. The mass concentration of oil was measured with an infrared spectrophotometer to calculate the oil removal rate. The results are as follows: Figure 5 shown.
[0072] Among them, the double core-shell structure photocatalyst is modified with nanographene NiCo 2 S 4 For the nuclear body;
[0073] Titanium dioxide is used as the middle shell;
[0074] Perovskite-type oxide Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05 O 3 For the outer shell layer;
[0075] The preparation method of the double core-shell structure photocatalyst is as follows:
[0076] 20mmol of cobalt nitrate hexahydrate, 10mmol of nickel nitrate hexahydrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, and mechanically stirred for 30min to make the mixture uniform, and then 0.5g of nanographene was added, and the mixture was sealed and heated to 180°C for hydrothermal reaction for 8h, and then returned to room temperature, and the product was collected, washed repeatedly with deionized water and anhydrous ethanol, and then dried, and then placed in a muffle furnace and heated to 350°C at a rate of 5°C / min and kept warm for 2h to obtain a core body;
[0077] 10 ml of butyl titanate was dropped into 35 ml of anhydrous ethanol, and stirred for 10 min to mix evenly to obtain liquid A. 10 ml of deionized water was added to another 35 ml of anhydrous ethanol, and stirred for 10 min. Then, glacial acetic acid was added to obtain liquid B with a pH of 2. Liquid B was kept stirred, and liquid A was slowly dropped into liquid B. After the dropping was completed, stirring was continued for 30 min. Then, stirring was stopped and the mixture was placed in a constant temperature water bath at 45°C for 30 min to obtain a titanium dioxide precursor impregnation solution. 1 g of the core was placed in the titanium dioxide precursor impregnation solution, and immersed for 10 min. Then, the intermediate was taken out and dried.
[0078] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 2.5mmol cerium nitrate hexahydrate was dissolved in 20ml deionized water to obtain liquid E, 95mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid F, 2.5mmol zirconium isopropoxide was dropped into 20ml anhydrous ethanol to obtain liquid G, liquid C, liquid D and liquid E were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, and After liquid F and liquid G are evenly mixed, 5 ml of ethylene glycol ethyl ether is added to obtain a second mixed solution. The first mixed solution is kept stirring, and the second mixed solution is slowly dripped into the first mixed solution. After the dripping is completed, the stirring reaction is continued for 30 minutes, and then the stirring is stopped and placed in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution. The intermediate is placed in the perovskite oxide precursor impregnation solution and immersed for 10 minutes. After taking out and drying, it is transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2 hours.
[0079] Comparative Example 1:
[0080] The same as Example 1, except that the catalyst used is nanographene-modified FeCo 2 S 4 As the core, the perovskite oxide Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05O 3 For the shell.
[0081] The preparation method of the catalyst is as follows:
[0082] 20mmol of cobalt nitrate hexahydrate, 10mmol of ferric nitrate nonahydrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, and mechanically stirred for 30min to make the mixture uniform, and then 0.5g of nanographene was added, and the mixture was sealed and heated to 180°C for hydrothermal reaction for 8h, and then returned to room temperature, and the product was collected, washed repeatedly with deionized water and anhydrous ethanol, and then dried, and then placed in a muffle furnace and heated to 350°C at a rate of 5°C / min and kept warm for 2h to obtain a core body;
[0083] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 2.5mmol cerium nitrate hexahydrate was dissolved in 20ml deionized water to obtain liquid E, 95mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid F, 2.5mmol zirconium isopropoxide was dropped into 20ml anhydrous ethanol to obtain liquid G, liquid C, liquid D and liquid E were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, and After liquid F and liquid G are evenly mixed, 5 ml of ethylene glycol ethyl ether is added to obtain a second mixed solution. The first mixed solution is kept stirring, and the second mixed solution is slowly dripped into the first mixed solution. After the dripping is completed, the stirring reaction is continued for 30 minutes, and then the stirring is stopped and placed in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution. The intermediate is placed in the perovskite oxide precursor impregnation solution and immersed for 10 minutes. After taking out and drying, it is transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2 hours.
[0084] Comparative Example 2:
[0085] The same as Example 1, except that the catalyst used is nanographene-modified FeCo 2 S 4 It is the core and titanium dioxide is the shell.
[0086] The preparation method of the catalyst is as follows:
[0087] 20mmol of cobalt nitrate hexahydrate, 10mmol of ferric nitrate nonahydrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, and mechanically stirred for 30min to make the mixture uniform, and then 0.5g of nanographene was added, and the mixture was sealed and heated to 180°C for hydrothermal reaction for 8h, and then returned to room temperature, and the product was collected, washed repeatedly with deionized water and anhydrous ethanol, and then dried, and then placed in a muffle furnace and heated to 350°C at a rate of 5°C / min and kept warm for 2h to obtain a core body;
[0088] Drop 10 ml of butyl titanate into 35 ml of anhydrous ethanol, stir for 10 minutes to mix evenly to obtain liquid A, take 10 ml of deionized water and add it to another 35 ml of anhydrous ethanol, stir for 10 minutes, then add glacial acetic acid to obtain liquid B with a pH of 2, keep liquid B stirring continuously, slowly drop liquid A into liquid B, continue stirring and react for 30 minutes after dropping, then stop stirring and place in a constant temperature water bath at 45°C for 30 minutes to obtain a titanium dioxide precursor impregnation solution, take the above 1 g of the core body and place it in the titanium dioxide precursor impregnation solution for 10 minutes, then take it out and dry it, then transfer it to a muffle furnace and heat it to 600°C at a rate of 5°C / min and keep it warm for 2 hours.
[0089] Comparative Example 3:
[0090] The method is basically the same as Example 1, except that the catalyst used uses commercially available titanium dioxide as the core;
[0091] Perovskite-type oxide Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05 O 3 For the shell.
[0092] The preparation method of the catalyst is as follows:
[0093] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 2.5mmol cerium nitrate hexahydrate was dissolved in 20ml deionized water to obtain liquid E, 95mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid F, 2.5mmol zirconium isopropoxide was dropped into 20ml anhydrous ethanol to obtain liquid G, liquid C, liquid D and liquid E were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, and liquid F and liquid E were mixed. After the G liquid is mixed evenly, 5 ml of ethylene glycol ethyl ether is added to obtain a second mixed solution. The first mixed solution is kept stirring, and the second mixed solution is slowly dripped into the first mixed solution. After the dripping is completed, the stirring reaction is continued for 30 minutes, and then the stirring is stopped and placed in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution. 1 g of commercially available titanium dioxide is placed in the perovskite oxide precursor impregnation solution and immersed for 10 minutes. After taking out and drying, it is transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2 hours.
[0094] Comparative Example 4:
[0095] The method is basically the same as Example 1, except that nanographene is not added when the core of the double core-shell structure photocatalyst is prepared;
[0096] The double core-shell structure photocatalyst is based on FeCo 2 S 4 For the nuclear body;
[0097] Titanium dioxide is used as the middle shell;
[0098] Perovskite-type oxide Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05 O 3 For the outer shell.
[0099] The preparation method of the double core-shell structure photocatalyst is as follows:
[0100] 20mmol of cobalt nitrate hexahydrate, 10mmol of ferric nitrate nonahydrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, mechanically stirred for 30min to make the mixture uniform, sealed and heated to 180°C for hydrothermal reaction for 8h, restored to room temperature, collected the product, washed repeatedly with deionized water and anhydrous ethanol and dried, then placed in a muffle furnace and heated to 350°C at a rate of 5°C / min and kept warm for 2h to obtain a core body;
[0101] 10 ml of butyl titanate was dropped into 35 ml of anhydrous ethanol, and stirred for 10 min to mix evenly to obtain liquid A. 10 ml of deionized water was added to another 35 ml of anhydrous ethanol, and stirred for 10 min. Then, glacial acetic acid was added to obtain liquid B with a pH of 2. Liquid B was kept stirred, and liquid A was slowly dropped into liquid B. After the dropping was completed, stirring was continued for 30 min. Then, stirring was stopped and the mixture was placed in a constant temperature water bath at 45°C for 30 min to obtain a titanium dioxide precursor impregnation solution. 1 g of the core was placed in the titanium dioxide precursor impregnation solution, and immersed for 10 min. Then, the intermediate was taken out and dried.
[0102] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 2.5mmol cerium nitrate hexahydrate was dissolved in 20ml deionized water to obtain liquid E, 95mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid F, 2.5mmol zirconium isopropoxide was dropped into 20ml anhydrous ethanol to obtain liquid G, liquid C, liquid D and liquid E were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, and After liquid F and liquid G are evenly mixed, 5 ml of ethylene glycol ethyl ether is added to obtain a second mixed solution. The first mixed solution is kept stirring, and the second mixed solution is slowly dripped into the first mixed solution. After the dripping is completed, the stirring reaction is continued for 30 minutes, and then the stirring is stopped and placed in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution. The intermediate is placed in the perovskite oxide precursor impregnation solution and immersed for 10 minutes. After taking out and drying, it is transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2 hours.
[0103] Comparative Example 5:
[0104] It is basically the same as Example 1, except that Bi 0.5 Na 0.5 TiO 3 Replace Bi 0.5 Na 0.5 Ti 0.95 (Zr 0.5 Ce 0.5 ) 0.05 O 3 .
[0105] Double core-shell structure photocatalyst with nanographene modified FeCo 2 S 4 For the nuclear body;
[0106] Titanium dioxide is used as the middle shell;
[0107] Perovskite-type oxide Bi 0.5 Na 0.5 TiO 3For the outer shell.
[0108] The preparation method of the double core-shell structure photocatalyst is as follows:
[0109] 20mmol of cobalt nitrate hexahydrate, 10mmol of ferric nitrate nonahydrate and 40mmol of thioacetamide were dissolved in a mixed solution consisting of 550ml of N-methylpyrrolidone and 50ml of deionized water, and mechanically stirred for 30min to make the mixture uniform, and then 0.5g of nanographene was added, and the mixture was sealed and heated to 180°C for hydrothermal reaction for 8h, and then returned to room temperature, and the product was collected, washed repeatedly with deionized water and anhydrous ethanol, and then dried, and then placed in a muffle furnace and heated to 350°C at a rate of 5°C / min and kept warm for 2h to obtain a core body;
[0110] 10 ml of butyl titanate was dropped into 35 ml of anhydrous ethanol, and stirred for 10 min to mix evenly to obtain liquid A. 10 ml of deionized water was added to another 35 ml of anhydrous ethanol, and stirred for 10 min. Then, glacial acetic acid was added to obtain liquid B with a pH of 2. Liquid B was kept stirred, and liquid A was slowly dropped into liquid B. After the dropping was completed, stirring was continued for 30 min. Then, stirring was stopped and the mixture was placed in a constant temperature water bath at 45°C for 30 min to obtain a titanium dioxide precursor impregnation solution. 1 g of the core was placed in the titanium dioxide precursor impregnation solution, and immersed for 10 min. Then, the intermediate was taken out and dried.
[0111] 50mmol sodium nitrate was dissolved in 100ml deionized water to obtain liquid C, 50mmol bismuth nitrate pentahydrate was dissolved in 100ml deionized water to obtain liquid D, 100mmol butyl titanate was dropped into 250ml anhydrous ethanol to obtain liquid E, liquid C and liquid D were mixed evenly, and then 45ml glacial acetic acid was added to obtain a first mixed solution, 5ml ethylene glycol ethyl ether was added to liquid E to obtain a second mixed solution, the first mixed solution was kept stirred, and the second mixed solution was slowly dropped into the first mixed solution. After the dropping was completed, the stirring reaction was continued for 30min, and then the stirring was stopped and placed in a constant temperature water bath at 45°C for 30min to obtain a perovskite oxide precursor impregnation solution. The intermediate was placed in the perovskite oxide precursor impregnation solution for 10min, taken out and dried, and then transferred to a muffle furnace and heated to 600°C at a rate of 5°C / min and kept warm for 2h.
[0112] Performance testing:
[0113] The oil removal rate results of the photocatalytic treatment method for treating industrial oily wastewater for 60 minutes in Examples 1-4 and Comparative Examples 1-5 are shown in Table 1 below:
[0114] ;
[0115] As can be seen from Table 1 above, the photocatalytic treatment method provided by the present invention has an excellent treatment effect on industrial oily wastewater;
[0116] From the data comparison of Examples 1-4, it can be seen that when the bimetallic sulfide MCo 2 S 4 When M is Fe, Ni, Cu, or Zn, the catalyst has an excellent treatment effect on industrial oily wastewater;
[0117] From the data comparison of Example 1 and Comparative Examples 1-3, it can be seen that changing the catalyst to a single-layer core-shell structure will result in a decrease in the treatment effect of industrial oily wastewater;
[0118] From the data comparison between Example 1 and Comparative Examples 4-5, it can be seen that whether it is the addition of nanographene or (Zr 0.5 Ce 0.5 ) 4+ The doping has played a positive role in improving the treatment effect of industrial oily wastewater.
[0119] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for photocatalytic treatment of industrial oily wastewater, characterized in that: Adding double core-shell structure photocatalyst to industrial oily wastewater and continuously providing light for photocatalytic treatment; The double core-shell structure photocatalyst uses a double metal sulfide as a core; Titanium dioxide is used as the middle shell; The outer shell layer is a perovskite-type oxide; The bimetallic sulfide is MCo2S4; Wherein, M is any one of Fe, Ni, Cu, and Zn; The structural formula of the perovskite oxide is as follows: Would 0.5 On 0.5 You 1-x (See 0.5 If 0.5 ) x About 3; Among them, 0<x≤0.
1.
2. The photocatalytic treatment method for industrial oily wastewater according to claim 1, characterized in that: The bimetallic sulfide is modified by a carbon material.
3. The photocatalytic treatment method for industrial oily wastewater according to claim 2, characterized in that: The carbon material is carbon nanotube and / or nanographene.
4. The photocatalytic treatment method for industrial oily wastewater according to claim 3, characterized in that: 0.04≤x≤0.06。 5. The method for photocatalytic treatment of industrial oily wastewater according to any one of claims 2 to 4, characterized in that: The preparation method of the double core-shell structure photocatalyst is as follows: The water-soluble cobalt salt, the water-soluble M salt and the thioacetamide are dissolved in the N-methylpyrrolidone / water mixed solution, and then the carbon material is added, and the temperature is raised to 160-180°C for hydrothermal reaction for 5-10 hours in a sealed state, and the product is collected, washed with deionized water and anhydrous ethanol and dried, and then annealed at 350-450°C for 1-5 hours to obtain a core body, and then a titanium dioxide precursor impregnation solution and a perovskite oxide precursor impregnation solution are prepared respectively by the solution gel method, and the core body is successively impregnated in the titanium dioxide precursor impregnation solution and the perovskite oxide precursor impregnation solution, dried and then heat treated.
6. The photocatalytic treatment method for industrial oily wastewater according to claim 5, characterized in that: The heat treatment temperature is 550-650℃.
7. The photocatalytic treatment method for industrial oily wastewater according to claim 1, characterized in that: The dosage of the double core-shell structure photocatalyst is 0.1-1 g / L.
Citation Information
Patent Citations
Bi2Ti2O7 ceramic powder and preparation method thereof
CN107381635A
Perovskite type composite photocatalyst and preparation method thereof, and special system and method
CN113663679A